2014
DOI: 10.1007/s40519-014-0110-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary macronutrient composition on eating behaviour and self-perception in young women undergoing weight management

Abstract: The control of eating behaviours such as hunger and disinhibition is problematic for women during weight management. Higher-protein (HP) diets have been shown to promote greater weight reduction than higher-carbohydrate (HC) diets, but their impact on eating behaviours is relatively unexplored. This study compared two iso-energetically restricted (5,600 kJ/day) diets differing in protein (HP: 32%, HC: 20%) and carbohydrate (HP: 41%, HC: 58%) on appetite ratings, restraint, disinhibition, perceived hunger and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
1
17
1
Order By: Relevance
“…The eating behavior trait profiles of individuals undergoing weight loss intervention are clearly of high importance, as the eating behavior response of an individual can determine their weight loss success. There are robust findings that in following weight loss interventions, a change in eating behavior traits are seen, whereby there is an increase in Restraint [77, 78] [52, 79, 80] and a decrease in Disinhibition (or UE) [81, 82] [52, 79, 80] and Hunger [8387]. However, one study found no change in TFEQ factors despite significant weight loss [60].…”
Section: Eating Behavior Traits and Weight Loss Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The eating behavior trait profiles of individuals undergoing weight loss intervention are clearly of high importance, as the eating behavior response of an individual can determine their weight loss success. There are robust findings that in following weight loss interventions, a change in eating behavior traits are seen, whereby there is an increase in Restraint [77, 78] [52, 79, 80] and a decrease in Disinhibition (or UE) [81, 82] [52, 79, 80] and Hunger [8387]. However, one study found no change in TFEQ factors despite significant weight loss [60].…”
Section: Eating Behavior Traits and Weight Loss Interventionsmentioning
confidence: 99%
“…In comparison, those studies which utilized, for example, the Mediterranean diet [83] and high-protein and high0carbohydrate diets [79], calorie restricting diets [88], and lifestyle intervention including dietary advice [80] saw increases in TFEQ Restraint and decreases in Disinhibition. Weight loss with these diets was associated with increases in Restraint [80, 88], decreases in Disinhibition [79], or both [83]. It is plausible that changes in eating behavior traits are associated with changes in appetite peptides, where TFEQ Hunger positively predicted ghrelin levels during weight loss [85].…”
Section: Eating Behavior Traits and Weight Loss Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low, normal and high scores may be classified as ≤5, 6-11, ≥12 for dietary restraint, ≤7, 8-12, ≥13 for disinhibition, ≤4, 5-8, ≥9 for hunger and ≤ 17, 18-26, ≥27 for binge eating. 28 Unanswered questions were scored as zero to summarize them together with the other questions answered, in calculating the total scores for the eating behaviours. The individual score was calculated and used in the analyses only if onehalf or more of the subscale questions were answered.…”
Section: Discussionmentioning
confidence: 99%
“…However, among women with obesity participating in a weight loss program no difference in eating behaviours between a high-protein and a high-carbohydrate diet was seen. 28 To our knowledge the influence of eating behaviours on weight gain during smoking cessation, while taking changes in the composition of the diet into consideration, has not been well studied. The aims of the present study were to compare eating behaviours (dietary restraint, disinhibition, hunger and binge eating) between two diets reduced in carbohydrate or fat and explore the relation between eating behaviours and weight change in men and women with overweight or obesity during smoking cessation with the aid of varenicline.…”
mentioning
confidence: 99%